Determination of Kinematic Parameters of Rotary Transmission Tooled with Hydraulic Cylinders; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Blashchuk M. Yu. Mikhail Yurievich; Kust T. S. Tatiana Sergeevna; Dubrovskiy M. V.; Lizunkov V. G. Vladislav Gennadyevich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen